Soil Contamination and Alternatives for Sustainable Development 2019
DOI: 10.5772/intechopen.81548
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Nitrous Oxide Emissions during Nitrification and Denitrification Processes in Agricultural Soils Using Enhanced Efficiency Fertilizers

Abstract: Through the increasing use of nitrogen (N) fertilizers due to an increasing food demand, the agricultural sector is the main contributor of anthropogenic nitrous oxide (N 2 O) emissions, mainly through microbial processes called nitrification and denitrification. One option to mitigate N 2 O, a major greenhouse gas, is to use enhanced efficiency fertilizers (EEFs). There are different types of EEFs like nitrification inhibitors or controlledrelease fertilizers that aim to match the N release from fertilizers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…High nitrification has been a concern for decades for the negative impact on the environment, due to high N losses via nitrate leaching which cause soil pollution or emission of nitrous oxide (N 2 O) through denitrification (Timilsena et al 2015;Uchida and von Rein 2018). Reducing nitrification rates in soils represents a strategy to mitigate the negative impact of nitrate to the environment (Subbarao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…High nitrification has been a concern for decades for the negative impact on the environment, due to high N losses via nitrate leaching which cause soil pollution or emission of nitrous oxide (N 2 O) through denitrification (Timilsena et al 2015;Uchida and von Rein 2018). Reducing nitrification rates in soils represents a strategy to mitigate the negative impact of nitrate to the environment (Subbarao et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of the ozone layer due to N2O is an important consideration beyond the concern for nitrogen losses from applied fertilizers and manures. Experiments have shown that both the processes of nitrification and denitrification contribute to the release of N2O from the soils into the atmosphere" [28]. N2O production is significantly influenced by soil water content, as water creates anaerobic conditions by reducing the oxygen diffusion rate by ten thousand times.…”
Section: Nitrous Oxidementioning
confidence: 99%
“… 1 In addition, these losses lead to a decline in nitrogen use efficiency (NUE) and environmental pollution. 2 It has been reported that NUE in alkaline calcareous soils is much lower (15–23%) 3 compared to non-calcareous soils (30–40%). 4 High soil pH, temperature, and low cation-exchange capacity (CEC) and organic matter content are the main causes of lower NUE in alkaline calcareous soils.…”
Section: Introductionmentioning
confidence: 97%
“…However, the plants do not utilize the excess N completely, and a considerable portion of applied N is lost as NH 3 -volatilization, NO 3 -leaching, and N 2 O emissions result in the wastage of resources and money . In addition, these losses lead to a decline in nitrogen use efficiency (NUE) and environmental pollution . It has been reported that NUE in alkaline calcareous soils is much lower (15–23%) compared to non-calcareous soils (30–40%) .…”
Section: Introductionmentioning
confidence: 99%